Approaching a critical turn? A content analysis of the politics of resilience in key bodies of resilience literature. Issue 2 (3rd May 2016) - Biermann, Maureen; Hillmer-Pegram, Kevin; Knapp, Corrine Noel; Hum, Richard E.
Abstract: Resilience thinking is increasingly used as both a theoretical framework and as a tool for managing and governing social and social–ecological systems. However, resilience may lead to undesirable outcomes if it fails to critically engage with issues of power, justice and equity, or what we call the politics of resilience. This potential pitfall can be addressed by incorporating critical theory, which aims to critique and transform historically inequitable social realities: a goal being actively pursued by scholars who publish in, inter alia, Resilience: International Policies, Practices and Discourses . In this article, we review the key critical claims about the politics of resilience established in this journal and then use a content analysis to test whether the journal Ecology & Society has made similar advances in integrating resilience thinking with critical perspectives on the politics of resilience. Our results suggest that Ecology & Society 's incorporation of critical theory has been minimal, but not completely absent. We identify possible explanations for this finding and discuss important benefits, challenges and strategies (both theoretical and pragmatic) associated with the ongoing interdisciplinary effort to bring together critical theory and resilience thinking.